Different PSMA Radiopharmaceuticals: A Comparative Study of [18F]F-PSMA-1007, [18F]F-JK-PSMA-7, and [99mTc]Tc-PSMA-I&S in the Skeletal System - Zsófia Sára Mikó; László Varga; István Farkas; Gyula Tóth; Kristóf Apró; Barnabás Márk Révész; Gábor Sipka; Péter Gergő Tompa; Annamária Bakos; Tamás Czékus; Mátyás Bukva; László Pávics; et al. (Pharmaceuticals)
Background: Numerous PSMA-based tracers are used for diagnostic prostate cancer imaging, but comprehensive comparisons between multiple ligands are lacking. This study aimed to compare physiological skeletal uptake and tracer uptake in commonly recommended PSMA reference regions across three different PSMA ligands in prostate cancer patients. Methods: A total of 281 prostate cancer patients were included. Using PET and SPECT imaging, target volumes of interest were defined via a semiautomatic method, and standardized uptake values (SUV) were calculated for the skeletal system and reference regions (liver, spleen, parotid gland, and blood pool). Results: Significant differences in SUV uptake were observed, with [18F]F-PSMA-1007 showing higher SUV values in the skeletal system. The parotid gland displayed the highest variability in uptake, while the blood pool and liver exhibited more homogeneous uptake across patients. Conclusions: While radioligands behave similarly in bone regions, there are notable differences in SUV patterns, particularly for PSMA-1007, which showed higher bone uptake. Parotid gland uptake variability suggests a reconsideration of its suitability as a reference region, while the liver, spleen, and blood pool showed more consistent uptake. During comparison, the technetium-labeled SPECT ligand proved as similarly effective as the two PET ligands for diagnostic imaging.